Iridium-mediated borylation of benzylic C-H bonds by borohydride. - Tang, C; Smith, W; Thompson, A; Vidovic, D; Aldridge, S (2011)
Simple source: An intramolecular iridium-mediated C-H borylation proceeds through transfer of a BH3 fragment from borohydride to a benzylic carbon center (see scheme; coe=cyclooctene). Simple and inexpensive LiBH 4 is thus utilized as the boron source in C-H to C-B conversion. © 2011 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.